Does mild internet use augment cognitive functions?: Preliminary evidence - R Archana; Manoj K Sharma; J Keshav Kumar; Palaniappan Marimuthu (Journal of Family Medicine and Primary Care, 2019)
Background: Internet usage leads to psychological disturbances, social problems, and neuropsychological dysfunctions. Alhough there is no definite trend has been reported for the association of augmentation of cognitive function and internet use pattern. Method: The current work explored the neuropsychological profile among healthy, mild, and moderate users of internet in the age group of 18 to 30 years. Sixty subjects (20 healthy internet users, 20 mild internet users, and 20 moderate internet users) were screened for internet usage using internet addiction test. Background datasheet, NIMHANS comprehensive battery of neuropsychological tests, and Wechsler memory scale III (Indian adaptation) were administered in an individual setting. Results: It revealed that mild users have performed relatively better than healthy normal controls on mental speed, sustained attention, cognitive switch, and interference scores on Stroop test. Conclusions: It has implication for evolving psychological intervention for promotion of mild internet use for the promotion neuropsychological functioning as well as physicians at primary setting can educate users about benefits of mild use of the internet and other technology devices. It will help in the promotion of healthy use of technology.